Results of Hemiarthoplasty in Basicervical Fracture Neck of Femur (Gardon Type-III & IV) using Austin Moor Prosthesis and their Assessment in Terms of Charnley Hip Score and Harris Hip Score (Medical Forum Monthly, 2024)
Objective: To determine the long term results of Hemiarthoplasty with Austin Moor Prosthesis and to evaluate the results in terms of Harris hip score and Charnley hip score.Study Design: Experimental study. Place and Duration of Study: The study was conducted at Khawaja Muhammad Safdar Medical College/Allama Iqbal Memorial Teaching Hospital, Sialkot from January, 2001 to December, 2011.Materials and Methods: Total 55 patients 40 male (72.72%) and 15 female (27.27%) were selected for study after Hemiarthroplasty with Austin Moor Prosthesis in elderly patients. The age range from 60 to 95 years with an average age of 68 years. 34 patients (61.81%) had Gardon type-III and 21 patients (38.18%) had Gardon type-IV fracture neck of the femur.Results: Post operatively, all patients were assessed radiologically as well as clinically with dual assessment scale using Harris hip score (pain 44 point, function 47 point, deformity 4 point, range of motion 5 point) and Charnley hip score in terms of pain, movement and walking ability with scale of 1 to 6. One being totally disable and six being a normal status. According to H.H.S. we noted 78.18% excellent, 14.54% good and 7.27% poor result at five years follow up and 70.83% excellent, 14.58 good and 14.58% poor results between five to ten years follow up in our study. As per Charnley hip score scale we noted 96.85% satisfactory results and 3.63% poor results at five years follow up and 77.08% satisfactory results at 5 to 10 years follow up in our study. The complications noted during follow up include; infection in 5 patients (9.09%), pain 10 patients (18.18%) shortening in 03 patients (5.45%), scatic nerve injury with foot drop (0%). According to radiological assessment, we noted dislocation in 1 patient (1.08%), acetabulum protrusia in 2 patients (3.63%), osteolysis 5 patients (9.09%), calcar resorption 5 patients (9.05%), loosening of implant patients (12.72%)Conclusion: Hemiarthroplasy in type-III and IV Basicervical fracture at the neck of femur with Austin Moor Prosthesis is simple, safe and cost effective method with low incidence of mortality and morbidity in old age patients and gives safely 8 to 10 pain free years to the patients.